Aromaticities of Five Membered Heterocycles through Dimethyldihydropyrenes Probe by Magnetic and Geometric Criteria. (25th March 2015) - Maria,; Ayub, Khurshid
Abstract : Aromaticities of five membered heterocycles, containing up to three heteroatoms, are quantified through the dimethyldihydropyrene (DHP) probe. Bond fixation caused by the fusion of heterocycles to the dimethyldihydropyrene nucleus (DHPN) was measured by changes in the 1 H NMR chemical shifts (magnetic) and bond lengths alterations (structural criterion). Chemical shifts of dihydropyrenes were calculated at GIAO HF/6-31G(d)//B3LYP/6-31+G(d). For 1 H NMR chemical shift analysis, two nonaromatic reference models are studied. Among the studied heterocycles, pyrazole and triazole are about 80–85% aromatic relative to benzene, through both magnetic and geometric criteria. Thiazole and oxazoles are found least aromatic where quantitative estimates of aromaticities are about 34–42%, relative to benzene. These quantitative estimates of aromaticities of five membered heterocycles are also comparable to those from aromatic stabilization energies. The quantification of aromaticity through energetic, magnetic, and structural criteria can deliver the similar inferences provided that suitable reference systems are chosen.